Do Criminal Representatives Hinder or Improve Constituency Outcomes? Evidence from India - Nishith Prakash; Marc Rockmore; Yogesh Uppal (Institute for the Study of Labor (IZA), 2014)
The recent increase in the number of criminally accused politicians elected to state assemblies has caused much furor in India. Despite the potentially important consequences and the widely divergent views, the implications of their elections to state legislative assemblies on constituency-level economic performance are unknown. Using a regression discontinuity design and data on the intensity of night lights in satellite imagery at the constituency level, our results suggest that the cost of electing criminally accused politicians on measures of economic activity is quite large. Using estimates of the elasticity of GDP to light, we find that the election of criminally accused candidates lead to roughly 5 percent lower GDP growth per year on average. These estimated costs increase for candidates with serious accusations, multiple accusations, and accusations regarding financial crimes. Our result survives variety of robustness checks.
Keywords: D72; D73; O40; O12; 330; growth; Indian politicians; information disclosure; regression discontinuity; India